Research into Industrial Concentration in Europe - A Synopsis and Appraisal of Work Undertakenat Cranfield for the Commission of the European Communities. - Fishwick, Frank (Cranfield University, 1978)
This report is not a thesis for the degree of Ph. D. but is an "exposition" referred to in Regulation 14-9 of the Institute, which allows the presentation of published work on one particular theme, instead of an original thesis. The publications submitted with this exposition are the reports of four studies of the evolution of concentration in the United Kingdom - (i) in paper manufacture and conversion, (ii) certain parts of the textile industry, (iii) selected vehicle accessories and (iv) press and general publishing. These studies were undertaken under contract for the Commission of the European Communities and form part of an extensive research programme directed by the Directorate General for Competition. The four projects were undertaken over the period April 1974 to November 1977. For the first of these projects a full-time research associate (Mrs. W. Hull) was employed. She was responsible for most of the data collection and prepared the first draft of much of this report. The other three projects were my own exclusive responsibility and the texts of the reports were entirely written by me - assistance being confined to clerical staff for data collection and a research assistant for data processing. Mr. Robert Cornu negotiated the first two of the contracts and assisted in communication with the predominantly French-speaking liaison staff in Brussels but he was not involved in any of the actual investigations. The four projects were undertaken in accordance with guidelines prescribed by the Directorate General for Competition. These guidelines changed over the 1974-7 period and this is reflected in the reports. Because the statistical framework and methods of analysis were defined by the Commission, the investigations and the reports do not entirely reflect my own views on the analysis of concentration. For this reason this exposition of the work is of somewhat greater length than that which Regulation 14-9 appears to imply. Chapter One contains an explanation of the Commission's interest in concentration as an aspect of market dominance, followed by summaries of the relevant literature and of empirical research into the effects of concentration. The objective of this chapter is to place the studies financed by the Commission into the context of economic theory and recent research by industrial economists. Chapter Two examines problems of definition and of sample design in investigations of this kind. Chapter Three presents and compares indices of concentration based on the entire sample of firms. Chapter Four is concerned with the statistical analysis of oligopoly and concentrates particularly upon the innovative parts of the Commission's methodology. Chapter Five is a preliminary assessment of the value of the studies and contains some tentative suggestions for changes in the existing approach. Throughout this exposition I have drawn evidence from the four reports but have only occasionally quoted from any, of the large number (over 100) reports completed by other research organisations in the nine member countries of the European Economic Community. I have estimated the total cost of this research programme at December 1977 prices and up to that date to be around £1.2 millions.